(untitled) (Journal of the College of Basic Education, 2023)
Security of data communication becomes a crucial challenge due to the rapid development of computer and information technologies. To ensure security of resource transmission, computer engineers have proposed numerous schemes for protection among them, the remote user authentication schemes using smart cards are regarded as very efficient. Remote user authentication has been adopted as one of the most commonly used solutions in network environments to protect resources from unauthorized access. As a result, smart-card based authentication schemes has become a popular research topic in recent years. So we propose a system about remote user-authentication that aims to achieve more functionality these schemes is secure and works like a close channel because ID user and password is required to authenticate the user, so we fulfill the basic need of authentication schemes. Furthermore, the proposed scheme provides the following properties: establish a session key, mutual verification, easy-of-use, without verification table and based on public key encryption.